Theologies of the Cross and the Mysteries of God: Apostolic Weakness and Divine Power in the Literary Receptions of 1 Cor 2:1-8 - de Assis, Jean Felipe (TEOLITERARIA - Revista de Literaturas e Teologias, 2016)
This last essay of a three-part research on early Jewish-Christian traditions and Gnostic movements examines the reception of 1 Cor 2:1-16. Taking into consideration the Pauline Theology of the Cross, which emphasizes apostolic weakness; and revelations of the mysteries of God to those who were called perfect Christians, which provides empowerment through contemplation of this unveiling. There is an apparent ambiguity in Paul’s arguments with many parallels in the gnostic traditions, apostolic fathers and other patristic texts. There are two clear sections on the textual reference used in this article, representing multiple interpretations throughout Pauline traditions, and revealing a polyphonic situation with ambivalent categories. These two studied sections disclose a polyphonic situation in which opposite perspectives co-exist in religious or cultural expressions. These diverse receptions, attestations and interpretations of the Pauline ideas are natural developments in a complex system of communication, while also requiring a profound dialogue between literary methodologies and theological discourses. Even though scholars are unable to date particular texts and relate them to historical contexts, studies on literary receptions, rhetorical criticisms and ancient textual communications are crucial for the intersections between Religious Studies and Literature.